1980
DOI: 10.2307/3280403
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Tissue Culture Cells with Bloodstream Trypomastigotes of Trypanosoma cruzi

Abstract: Infection of tissue culture ("Vero" and bovine embryo skeletal muscle cells) with bloodstream from of T. cruzi depends on an adequate serum concentration and a suitable parasite population. The percentages of infections of "Vero" cells obtained with inocula presenting about 90% (Y strain) and 2% (CL strain) of slender trypomastigotes wree 11.8 +/- 4.9% and 0.1%, respectively, strongly indicating that the presence of slender forms was essential for cell infection to occur. Nevertheless, other biological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…When T. cruzi has been observed during the in vitro host-paratise interaction, varied results have been obtained: metacyclic forms of the Dm 28c clone, obtained after 72-96 hr of differentiation in an axenic medium are able to associate to 30-60% of heart muscle or fibroblastic cells within 2 hr of parasite contact and 30-50% of the associated parasites are already interiorized (Contreras et al 1988). Indeed, authors working with bloodstream trypomasytigotes and non-professional phagocytic cells like VERO or BEMS cells (Bertelli & Brener 1980), fibroblasts (Kongtong & Inoki 1975), primary heart or skeletal muscle cells ) pointed out to the need of at least 9-24 hr of parasite contact to obtain indexes varying between 1 and 9% of infected cells, depending on the parasite strain used. Comparative studies between T. rangeli and T. cruzi strains are controversial due to the heterogeneity of clonal populations within a T. cruzi strain (Deane et al 1984, Dvorak 1984, Tibayrenc & Ayala 1988, De Diego et al 1991, Penin et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…When T. cruzi has been observed during the in vitro host-paratise interaction, varied results have been obtained: metacyclic forms of the Dm 28c clone, obtained after 72-96 hr of differentiation in an axenic medium are able to associate to 30-60% of heart muscle or fibroblastic cells within 2 hr of parasite contact and 30-50% of the associated parasites are already interiorized (Contreras et al 1988). Indeed, authors working with bloodstream trypomasytigotes and non-professional phagocytic cells like VERO or BEMS cells (Bertelli & Brener 1980), fibroblasts (Kongtong & Inoki 1975), primary heart or skeletal muscle cells ) pointed out to the need of at least 9-24 hr of parasite contact to obtain indexes varying between 1 and 9% of infected cells, depending on the parasite strain used. Comparative studies between T. rangeli and T. cruzi strains are controversial due to the heterogeneity of clonal populations within a T. cruzi strain (Deane et al 1984, Dvorak 1984, Tibayrenc & Ayala 1988, De Diego et al 1991, Penin et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Bloodstream trypomastigotes were obtained from infected Vero cells as described by Bertelli et al [26].…”
Section: Parasites and Growth Of T Cruzi Epimastigotes And Bloodstrementioning
confidence: 99%
“…Infection studies with Vero and muscle cells demonstrated that slender forms are necessary for cell infection. 71 The broad forms do not infect vertebrate cells but can develop in the triatomid vector. This situation resembles that which occurs in bruceisubgroup trypanosomes, in which stumpy forms show a greater infectivity for the tsetse vector than the slender bloodstream forms.…”
Section: Vertebrate Formsmentioning
confidence: 99%